The Energy Quality of Some Bamboo Varieties - Phuangchik, Thanpisit (Thai Journal of Science and Technology, 2024)
The aim of this study was to study the energy quality of 3 year age bamboo 7 varieties, including sang nuan bamboo (Dendrocalamus membranaceus Munro), sang mon bamboo (Dendrocalamus sericeus Munro), pao mae tawo bamboo (Dendrocalamus copelandii1), man moo bamboo [Dendrocalamus copelandii (Gamble ex Brandis) N.H. Xia & C.M.A. Stapleton2], beijing bamboo (Dendrocalamus sp.), ruak bamboo (Thyrsostachys siamensis) and liang yai bamboo (Bambusa sp.) by leading bamboos part go through carbonization temperature of 600-700 ˚C then grind to a find powder. The determination of the physical and chemical properties of charcoal such as thermal analysis, moisture, ash, volatile, fix carbon and element mass fraction were studied. The results showed that man moo bamboo had the highest heating value and fix carbon, 30.4 MJ/Kg and 53.07%, respectively. sang nuan bamboo showed the least ash content 8.58% and found the least volatile in beijing bamboo at 25.45%. Therefore, the most suitable bamboo for energy quality base on heat value and fix carbon was man moo bamboo, sang nuan bamboo and beijing bamboo, respectively.